Effect of plant number per hill in sunflower - Fleck, Nilson Gilberto; Silva, Paulo Regis Ferreira da (Pesquisa Agropecuaria Brasileira, 2014)
In order to evaluate the effects of number of plants per hill on sunflower (Helianthus annuus L.) grain yield, yield component, and on other agronomic traits, two field experiments were carried out in Guaíba, RS, Brazil. In the first year, treatments consisted of one, two, three, and four plants per hill. In the second year, a fifth treatment was added, with plants disposed in a completely randomized way in the row. ln each year, rate of planting and row spacing were the same for all treatments. Results of the two years indicated that grain yields did not vary significantly within treatments. However, there was a trend that the treatments with three and four plants per hill presented lower grain yields than the others with only one or two plants per hill. Grain number per head was the yield component that showed the highest correlation with grain yield, decreasing as the number of plants per hill increased. Plant height was affected by treatments only in the first year, when it was reduced as the number of plants par hill increased. On the other hand, the effect of plant distribution in the row on head diameter was only observed in the second year, when this trait decreased with the increase in the number of plants per hill.